Clinical skills for medical students - Kabraji, Sheheryar (Scion, 2012)
Clinical Skills for Medical Students covers virtually all the skills that are taught and examined at medical school. The clear and concise text, attractive layout, and numerous tables and figures make it very easy for medical students, junior trainees, and other healthcare professionals to prepare for clinical examinations and/or succeed in clinical practice. Key features include: * Step-by-step instructions for a broad range of clinical skills; * Detailed coverage of difficult areas such as blood transfusion and orthopedic examinations; * Detailed coverage of the medical conditions that are most likely to come up in clinical exams; * Special boxes headed 'Junior Resident's Tips' and 'Senior Resident's Questions' to focus attention on important or frequently examined areas; * Evidence-based approach with likelihood ratios published alongside key clinical findings; * A hints and tips section to maximize exam performance. Clinical Skills for Medical Students will make your life easier and save you a lot of time.